(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Today’s Russian market of tourist services is very diverse and demonstrates, according to experts, very positive development trends. However, neither natural nor cultural sites alone do not make a region attractive to tourists. Unfortunately, the level of tourist services leaves much to be desired, and where it is high, the price is above the average, since with restrictions on travel abroad the people have not many alternatives. The creation of an interaction model for all the participants of the travel market based on User Agreement and, as a consequence, the creation of communicative tools, such as mobile applications and phone calls, is the aim of the current research. The methodology is based on a set of methods, including analogy, comparison, programming, and modeling. Given the results, a new approach to promoting rural tourism will not only attract funds to small towns and villages but also contribute to the development of recreational systems and make traveling in Russia comfortable for both domestic and foreign tourists.